Ionic Current Fluctuation and Orientation of Tetrahedral DNA Nanostructures in a Solid‐State Nanopore. Issue 12 (29th January 2022) - Chen, Xiaoyu; Zhao, Xinjia; Ma, Ruiping; Hu, Ying; Cui, Chengjun; Mi, Zhuang; Dou, Ruifen; Pan, Dun; Shan, Xinyan; Wang, Lihua; Fan, Chunhai; Lu, Xinghua
Abstract: Understanding the dynamic behavior of a nanostructure translocating through a nanopore is important for various applications. In this paper, the characteristics in ion current traces of tetrahedral DNA nanostructures (TDN) translocating through a solid‐state nanopore are examined, by combined experimental and theoretical simulations. The results of finite element analysis reveal the correlation between orientation of TDN and the conductance blockade. The experimentally measured fluctuations in the conductance blockade, expressed as voltage‐dependent histogram profiles, are consistent with the simulation, revealing the nature of a random distribution in orientation and weak influence of electrostatic and viscous torques. The step changes in orientation of a TDN during translocation are further explained by the collision with the nanopore, while the gradual changes in orientation illustrate the impact of a weak torque field in the nano‐fluidic channel. The results demonstrate a general method and basic understanding in the dynamic behavior of nanostructures translocating through solid‐state nanopores. Abstract : In this article, the dynamic behavior of tetrahedral DNA nanostructures during translocation through a solid‐state nanopore is examined by experimental and theoretical simulations. The correlation between orientation of the nanostructure and the conductance blockade is illustrated. The nature of a random orientation distribution, collision with nanopore wall, and weak influence of torque fields, are revealed.